I want to be somebody new! - Lopshire, Robert (Canada : Beginner Books, 1986)
Tired of doing tricks in a circus, a large spotted animal decides he wants to be something different such as a mouse, an elephant, or a giraffe.
Keywords: Animals - Fiction; Self-acceptance - Fiction; Stories in rhyme